Optimizing Motorcycle Combustion System for Carbon Monoxide Emission Reduction Using the Taguchi Method - Lailatus Sa’diyah Yuniar Arifianti; Ata Syifa’ Nugraha; Sudirman Rizki Ariyanto; Muhammad Rasyid Ridho (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2025)
In Indonesia, the dominance of motorcycles as the primary mode of transportation has created a significant urban air quality crisis, largely driven by exhaust emissions. Carbon monoxide (CO), a key indicator of incomplete combustion, poses a serious risk to public health and the environment. While previous studies have examined engine parameters such as spark plugs, ignition coils, or fuel quality in isolation, this study addresses a critical gap by shifting from single-factor analysis to a holistic, multi-parameter optimization. This approach is unique in its application of the Taguchi Method to identify a robust, real-world solution specifically tailored to the Indonesian context. We systematically optimized a motorcycle’s combustion system by evaluating three key parameters—fuel type, spark plug type, and ignition coil—at three levels each. Using an L9 Orthogonal Array and a smaller-the-better Signal-to-Noise (S/N) ratio, we aimed to minimize CO emissions. The results identified an optimal configuration of Mobil-brand fuel, an NGK Iridium spark plug, and a Suzuki A100 coil, which achieved a 42.03% reduction in CO emissions compared to the standard setup. Analysis of Variance (ANOVA) confirmed that fuel quality is the overwhelmingly dominant factor, contributing nearly 90% to the outcome. These findings provide a practical, low-cost emission control strategy with direct policy relevance for Indonesia, offering a clear path for vehicle maintenance shops and owners to contribute to cleaner air and support sustainable transportation goals.